2021
DOI: 10.1007/s00018-020-03733-2
|View full text |Cite
|
Sign up to set email alerts
|

An emerging potential of metabolomics in multiple sclerosis: a comprehensive overview

Abstract: Multiple sclerosis (MS) is an inflammatory demyelinating disease of the nervous system that primarily affects young adults. Although the exact etiology of the disease remains obscure, it is clear that alterations in the metabolome contribute to this process. As such, defining a reliable and disease-specific metabolome has tremendous potential as a diagnostic and therapeutic strategy for MS. Here, we provide an overview of studies aimed at identifying the role of metabolomics in MS. These offer new insights int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 136 publications
0
36
0
2
Order By: Relevance
“…Lipid metabolites are currently believed to be useful biomarkers because of their dynamic profile changes in various conditions. The lipidomic approach may be beneficial in examining the effects of therapeutical interventions and has been suggested for use in monitoring in clinical therapeutic trials [ 10 ]. A few recently published studies explored this approach with regard to MS patients treated with DMT.…”
Section: Current and Future Lipids-based Therapeutical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid metabolites are currently believed to be useful biomarkers because of their dynamic profile changes in various conditions. The lipidomic approach may be beneficial in examining the effects of therapeutical interventions and has been suggested for use in monitoring in clinical therapeutic trials [ 10 ]. A few recently published studies explored this approach with regard to MS patients treated with DMT.…”
Section: Current and Future Lipids-based Therapeutical Implicationsmentioning
confidence: 99%
“…Lipids are not only substantially involved in the formation of myelin sheath (and thus could be a hallmark of demyelination and repair), but are also engaged in the cell signaling, in communication, and in transport in the CNS [ 8 ]. Thus, they seem likely candidates for biomarkers of processes underlying active and progressive phase of MS, as well as potential target for new, effective, and stage-specific therapeutic interventions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The art of metabolomics can be implicated to differentiate between a diseased vs. a nondiseased state; therefore, it has gained significant translational importance in MS studies for the possible development of MS associated surrogate biomarkers and to monitor the disease progression with or without a therapeutic intervention. A few studies have employed the untargeted metabolomics approach to identify MS patients' cardinal metabolic changes (Zahoor et al, 2021). However, most of the studies used a single platform with the ability to identify limited metabolites (Zahoor et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The biological process we have found is rather generic, as it is related to the secretion of signals into the extracellular medium from a cellular source, but without further details about the signal or the origin of the secretion. For the KEGG pathway, previous studies have shown the role of pathways associated with these amino acids in the modulation of the autoimmune response, as well as mechanisms of cytotoxicity and neuroprotection [61, 62]. However, these studies did not take into account sex as factor and did not detect its influence on these alterations.…”
Section: Discussionmentioning
confidence: 99%